Metabolic crosstalk between roots and rhizosphere drives alfalfa decline under continuous cropping - Ma, Yuanyuan; Zhou, Xiaoping; Shen, Yan; Ma, Hongbin; Xue, Quanhong (Frontiers in Plant Science, 2024)
Considerable biological decline of continuously cropped alfalfa may be tightly linked to rhizosphere metabolism. However, plant-soil feedbacks and age-related metabolic changes in alfalfa stands remain unexplored. The aim of this study was to identify the linkages of rhizosphere and root metabolites, particularly autotoxins and prebiotics, to alfalfa decline under continuous cropping. We performed liquid chromatography-mass spectrometry for non-targeted metabolomic profiling of rhizosphere soils and alfalfa roots in two-and six-year-old stands. Differentially abundant metabolites that responded to stand age and associated metabolic pathways were identified.Compared with bulk soils, rhizosphere soils were enriched with more triterpenoid saponins (e.g., medicagenic acid glycosides), which showed inhibitory effects on seed germination and seedling growth. These autotoxic metabolites were accumulated in the old stand age and their relative abundances were negatively correlated with plant growth, yield, and quality traits, as well as soil total nitrogen and alkali-hydrolyzable nitrogen concentrations. In contrast, prebiotic metabolites, represented by glycerolipids (e.g., glycerophosphocholine) and fatty acyls (e.g., colnelenic acid), were depleted in rhizosphere soils in the old stand. The relative abundances of glycerolipids and fatty acyls were positively correlated with plant traits and soil available phosphorus and alkalihydrolyzable nitrogen concentrations. Age-induced changes in the rhizosphere metabolome mirrored the reprogramming patterns of root metabolome. The pathways of terpenoid backbone biosynthesis and plant hormone signal transduction, as well as metabolism of galactose, glycerophospholipid and ɑ-linolenic acid in alfalfa roots were affected by stand age. The up-regulation of terpenoid backbone biosynthesis in alfalfa roots of old plants, which stimulated triterpenoid saponin biosynthesis and exudation. Rhizosphere accumulation of autotoxins was accompanied by depletion of prebiotics, leading to soil degradation and exacerbating alfalfa decline. This research aids in the development of prebiotics to prevent and manage continuous cropping obstacles in alfalfa.